EVIDENCIA SEROLÓGICA DE ANTICUERPOS CONTRA EL VIRUS DE LA RETICULOENDOTELIOSIS EN GALLINAS REPRODUCTORAS DE LIMA - Salas C., Elia (2005)
A total of 180 serum samples collected in the period of April to September, 2004 from 12 broiler breeder flocks and commercial layers older than 50 weeks of age from ten poultry farms were tested for the presence of Reticuloendotheliosis virus (REV) antibodies using a commercial ELISA test. Only 3 samples were positive to antibodies against REV; however, the optical densities of the 3 positive samples were higher than the negative controls but below to the positive controls. ELISA serologic testing is not definitive and, therefore, it can be concluded that the 12 flocks were negative to REV antibodies. On the other hand, further studies, such as isolation and identification of the virus, are required to achieve a definitive diagnosis.